Faktor-faktor Psikologis Perilaku Berhutang pada Karyawan Berpenghasilan Tetap - Renanita, Theda; Hidayat, Rahmat (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The purpose of this study is to understand the debt behavior based on internal factors, social factor and functional factors in the environment. Theory of planned behavior is used as theoritical base. The study was conducted to test the hypothesis that opinions toward debt behavior, subjective norms, and perceived behavioral control influence directly and / or indirectly to the debt behavior, where the intention act as a mediator between the exogenous variables to the dependent variable. Subjects of the study were 182 civil servants at City Government of Yogyakarta who participated voluntarily. Path analysis showed that debt behavior is influenced by debt intention with value of b=0.359, p=0.004 (p